Development of strength and power in qualified martial artists using plyometric training - Samborskiy, A. G.; Nikulin, I. N.; Gorodov, S. S.; Lopatin, I. I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the effect of deep jumps on the manifestation of power and the generation of strength in qualified martial artists involved in judo and sambo.